Ecological Analysis Of Nutritional Status Of Toddler In Indonesia - Saputra, Ivan (Jurnal Kesehatan, 2024)
Toddlers are one of the groups that are prone to experiencing nutritional problems.  This can inhibit the mental and physical growth of children and can subsequently have an impact on the next generation. The study was conducted to analyze the relationship between existing environmental variables and the nutritional status of toddlers based on provinces in Indonesia. Further analysis of secondary data from the 2022 Indonesia Nutrition Status Survey and the Central Statistics Agency of Indonesia. This study using quantitative method with univariate and correlation analyses. The unit of analysis in this study is all 34 provinces in Indonesia. The variables analyzed were the number of malnutrition prevalence, the number of poor people, and the level of education. There’s wide variability of the number of poor people. The greater the number of poor people, the greater the number of malnutrition events in toddlers. The number of poor people is positively related to the number of malnutrition events in toddlers, be it stunting, wasting, or underweight. Meanwhile, the level of education has no relationship with the prevalence of malnutrition toddlers. The results of this study are considered important as a policy basis to improve the poverty rate and strive for better economic development in Indonesia.  Keywords: education level, nutritional status of toddlers, poverty level